KEPEMIMPINAN PEMBELAJARAN BAHASA INGGRIS DI SMP NEGERI 1 NGRAMPAL - WAHYUNINGTYAS, TRI; , Prof. Dr. Bambang Sumardjoko; , Dr. Sumardi, M.Si (2015)
The purpose of this study is to describe leadership of teacher as an educator, a motivator and an evaluator of English learning at Junior High School 1 Ngrampal. This research is qualitative research. This location is Junior High School 1 Ngrampal. Data collection techniques use an interview technique, an observation and information of documentation. Meanwhile, data analysis techniques use data reduction, presentation of data and conclusions. This results of research are 1) characteristics of teacher leadership as an educators of English learning at the Junior High School 1 Ngrampal are manage the classroom that is conducive, prepare RPP of English suitable SK&KD, use props and instructional English, master English teaching materials, create interaction English learning is easy to understand students, is influence in the process learning in the classroom, and has an emphatic, an affable, an objective, a democratic, and a sportive. 2) Characteristics of teacher leadership as an motivators of English learning at the Junior High School 1 Ngrampal are give motivate that is beneficial for the development of education, particular the student who is taught it and environment, motive the student in the learning English, show an interest that is high in the learning English, raise someone's spirit and interest in the learning English, give the natural of compliment to any student success, and create the competition and the cooperation in the learning English in the classroom. 3) Characteristics of teacher leadership as an evaluators of English learning at the Junior High School 1 Ngrampal are analysis and evaluate each development the student in the learning English, give skor/the final result at the students after it is given test such as assignment or quiz, willing to take a decision in assessing the student an achievement, establish minimum criteria for completeness in learning English by the school and MGMP, is responsible for the achievement learning students, communicate assessment criteria for the percentage of the beginning of the semester, dared to comment that builds on the work of students, and provide an assessment of students with the cognitive, psychomotoric, and afective.